2014
DOI: 10.1097/dbp.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Internet Guidance on Time Out

Abstract: Objective Pediatricians are frequently asked to address parents’ behavioral concerns. Time out (TO) is one of the few discipline strategies with empirical support and is recommended by the American Academy of Pediatrics. However, correctly performed, TO can be a complex procedure requiring training difficult to provide in clinic due to time and cost constraints. The Internet may be a resource for parents to supplement information provided by pediatricians. The present study included evaluation of information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Many parents are unaware of the effects of IA among adolescents ( Wu et al, 2016 ). Owing to the lack of knowledge, parents may inadvertently promote excessive online activities (such as online gaming) by the children; in addition, lack of parental attention and interaction may also act as aggravating factors in promoting IA ( Drayton et al, 2014 ; Schneider et al, 2017 ). Moreover, family conflict also causes adolescents to seek diversion to the internet, which can lead to addiction ( Schneider et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many parents are unaware of the effects of IA among adolescents ( Wu et al, 2016 ). Owing to the lack of knowledge, parents may inadvertently promote excessive online activities (such as online gaming) by the children; in addition, lack of parental attention and interaction may also act as aggravating factors in promoting IA ( Drayton et al, 2014 ; Schneider et al, 2017 ). Moreover, family conflict also causes adolescents to seek diversion to the internet, which can lead to addiction ( Schneider et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research that examined TO implementation has included surveys of parents (Riley et al, 2017) and reviews of website information on TO (Drayton et al, 2014). A qualitative survey of 400 parents from the USA found that although a majority of parents reported using TO, many procedural elements were implemented incorrectly, and this was associated with parents' perception that TO was ineffective (Riley et al, 2017).…”
Section: Criticisms Of Time-out Usementioning
confidence: 99%
“…A qualitative survey of 400 parents from the USA found that although a majority of parents reported using TO, many procedural elements were implemented incorrectly, and this was associated with parents' perception that TO was ineffective (Riley et al, 2017). When parents viewed TO as ineffective, it was likely to be replaced with more harsh or coercive strategies (Drayton et al, 2014) or permissive parenting strategies. A review of 102 webpages on TO found that none included accurate information on empirically supported TO parameters (Drayton et al, 2014).…”
Section: Criticisms Of Time-out Usementioning
confidence: 99%
“…5 While online parenting information is plentiful (e.g., googling "help with child behavior problems" leads to over 600 million results), the degree to which available information is research-informed is highly variable. For instance, in 2015, Drayton et al 6 reviewed internet-based information about the common disciplinary practice time-out. 3 They found none of the websites provided information about time-out that is consistent with the evidence-based procedure; some webpages also described time-out as ineffective.…”
Section: Technology As An Important and Emerging Solutionmentioning
confidence: 99%